Pengaruh Activity Ratio, Leverage dan Firm Growth Terhadap Financial Distress (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2013-2017) - Nur Hafni Lubis; Dina Patrisia (Universitas Negeri Padang, 2019)
This research aims to analyze the effect of (1) activity ratio, (2) leverage and (3) firm growth onfinancial distress in manufacturing companies listed in Indonesia Stock Exchange. Thepopulation in this study are all manufacturing companies listed in Indonesia Stock Exchange.The sampling technique used purposive sampling and sample obtained as much as 119companies. Data used in this research are secondary ones which obtained from ICMD. Dataanalysis method used logistic regression analysis. This study found that Activity ratio (TATO),leverage (DR) and firm growth (SG) have significant effect in probability of financial distress.However, ITO RTO and LTDER have insignificant effect to financial distress. The result showedaccurately prediction as much as 89%.Keywords: Financial Distress, activity ratio, leverage, firm growth